Hawkmistress! - Bradley, Marion Zimmer; Copyright Paperback Collection (Library of Congress) (New York, NY : DAW Books, 1982)
Romilly uses her power to communicate with and control animals to aid the battle to depose the usurper of the throne of Darkover.
"Comes ... between Stormqueen and Two to conquer."--p. [4].
Keywords: Fantasy fiction, American; Darkover (Imaginary place) -- Fiction; Fantasy fiction